Urticaria 1 - Fine, Lauren (Henry Stewart Talks, 2016)
Appearance, features & prevalence of urticaria, Relationship between angioedema and urticaria, Quality of life and urticaria, Acute and chronic urticaria, Algorithm for evaluation/management of urticaria, Causes of urticaria: allergic (IgE) & non-allergic (non-IgE), Detailed history of urticaria in patients, Pseudoallergens, Food & drug exposures, Infections that may lead to urticaria, Isolating the triggers of urticaria, Differential diagnosis of urticaria